ChemInform Abstract: On the Crystal Structure of a Previously Unknown Anhydrous Zinc Hydroxide Sulfate. Issue 16 (March 2016) - Germann, Luzia S.; Dinnebier, Robert E.; Liu, Xin; Dong, Yaping; Li, Wu
Abstract: The crystal structure of 5[Zn(OH)2 ]·2[ZnSO4 ] is determined by powder XRD.